Perbandingan Antara Organizational Citizenship Behavior Dengan Tingkat Kematangan Dosen. Studi Pada Dosen Politeknik Negeri Banjarmasin - Nurfitriah, Nurfitriah; Maharani, Sari Hepy (INTEKNA informasi teknik dan niaga, 2018)
This research aims to find out whether lecturers with different maturity levels have different OCBs. Research was conducted on 120 lecturers of State Polytechnic of Banjarmasin. Data analysis was done descriptively and quantitatively using One Way ANOVA. The analysis shows that OCB differs at different maturity levels, the increase in OCB is proportional to the increase in maturity level.